Comparative Analysis Of Performance Of A STATCOM And A D-STATCOM On Nagpur 9 Bus Ring Main System - Udbhav Srivastava, Shubham Gangwar, Satyam Verma, Ujjwal, Kalpana Hazarika (International Journal of Advanced Science and Technology, 2020)
This paper presents the compare the power flow between STATCOM and D-STATCOM to improve the power quality of 132 KV 9 bus ring main system. In this paper Newton Raphson method is used for load flow calculation. To solve the load flow calculations an accurate model for D-STATCOM is derived. The simulation is done under MATLAB/SIMULINK for STATCOM and D-STATCOM. Through this paper, D-STATCOM has demonstrated excellent performance and effectively improved the power quality in distribution networks. Keywords: Newton Raphson Load Flow, Load Flow Study, FACTS Controller, Voltage Stability, STATCOM, D-STATCOM